Analysis of Changes In Creatine Kinase Myocardial Band (CK-MB) And F2-Isoprostane Levels After A 30 Km Cycling Event In The Makassar Bike Community - Maryam Marsuki; Irfan Idris; Djohan Aras; Andi Wardihan Sinrang; Ilhamjaya Patellongi; Nukhrawi Nawir (COMPETITOR: Jurnal Pendidikan Kepelatihan Olahraga, 2023)
This study aims to determine changes in levels of Creatine Kinase-Myocardial Band and F2-Isoprostane after a 30 km cycling event. This is a pre-experimental study on 30 subjects of male cyclists aged 30-60 years taken by purposive sampling method. The pretest was carried out the day before the 30 km cycling event, then the post-test was carried out 2 hours after the cycling event. Blood testing was done with an ELISA Kit. Data analysis using the Wilcoxon test showed significant changes in Creatine Kinase-Myocardial Band levels after a 30 km cycling event (p=0.003). Meanwhile, there was no significant change in F2-Isoprostane levels after the event (p=0.688). The results of the Spearman test showed that there was a correlation between changes in levels of creatine kinase-myocardial band with changes in levels of F2-Isoprostane (p=0.042).